PERANCANGAN AFIS 1.0 (AUTOMATIC FLASHLIGHT IDENTIFICATION SIGNAL) PADA KRI DENGAN MENGGUNAKAN METODE ETNOGRAFI DAN QFD - Febriyant, Tedi; Rooswirawan, Avianto (Journal of Industrial Engineering & Management Research, 2022)
As the spearhead of the Indonesian Navy at sea, the Indonesian Warships (KRI) always hold an exercise both internally to the Indonesian Navy and with other countries. One of the exercises that are often carried out is to carry out sending and receiving flashlight code signal messages between ships in a convoy of warships at sea. Each communication division personnel has an important role in running the flashlight passcode communication system which is currently still done manually so that errors often occur in sending and receiving flashlight password signaling news or are less accurate and slow. In manning the current flashlight tool in the KRI requires 6 (six) personnel and because of its location on the outer deck of the ship with the condition that the distance between ships in a convoy formation at sea is very close during training so that it is very impacted by the dangers of deep high radiation. In the long run, the personnel will feel the effect. On the other hand, the use of flashlight password signals is still often used because this method has a better level of confidentiality when compared to electronic communication tools in the KRI which are easily intercepted by the enemy. From the explanation above, we can see that the speed, accuracy and confidentiality of the existing tools are not maximized, while in terms of security and comfort are still a problem for KRI personnel in manning the current tools. so scientific research is needed to obtain a solution. Therefore, the focus of this research is to implement an automatic flashlight code signal system between ships in a convoy of warships at sea with the design of the AFIS 1.0 (Automatic Flashlight Identification Signal) tool which is able to increase the speed, accuracy and confidentiality of the tool as well as security and comfort. for KRI personnel in manning the equipment.